Definition of NPSLE: Does the ACR Nomenclature Still Hold? - Vivaldo, Jessica Fernandes; de Amorim, Jaqueline Cristina; Julio, Paulo Rogério; de Oliveira, Rodrigo Joel; Appenzeller, Simone (Frontiers in Medicine, 2018)
Systemic lupus erythematosus (SLE) patients have frequently neuropsychiatric manifestations. From the first description of coma in 1875, a variety of manifestations has been described to occur in SLE. However, the lack of standardization reduced the comparability of published studies. In 1999, the American College of Rheumatology published guidelines to define neuropsychiatric nomenclature in SLE. This was the first step towards uniform diagnostic criteria. Several studies have been published since then applying the ACR criteria and frequencies of different manifestations can now be compared between cohorts. Although these criteria are diagnostic, therapeutic approach to different manifestations varies according to nature and severity of the manifestations. Herby, we will review the different definition for NPSLE published, and determine advantages and limitation.